The Influence of Good Corporate Governance and Accounting Conservatism on Tax Avoidance (Empirical Study of Mining Companies Listed on the Indonesian Stock Exchange for the Period (2017-2020) - Rumapea, Bonia Ayunita; Sumarsan, Thomas; Simanjuntak, Arthur; Rumapea, Melanthon (PT FORMOSA CENDEKIA GLOBAL, 2024)
Tax is one of the state's rights which is coercive towards society. Income from the state can be increased through the tax system implemented in society. Potential sources of revenue come from the tax revenue system that has been implemented. The purpose of this writing is to analyze the influence of good corporate governance and accounting conservatism on tax avoidance. The type of research used is quantitative. The significance value obtained is 0.008 <0.05, this means that tax avoidance is influenced by accounting conservatism, audit committees, independent commissioners, and institutional ownership. The Adjusted R2 value obtained is 0.331, meaning the contribution of accounting conservatism, audit committee, independent commissioners and institutional ownership is 33.1%.